Cross-Sex Best Friendships and the Experience and Expression of Jealousy within Romantic Relationships. (2019) - Gilchrist-Petty, Eletra; Bennett, Lance Kyle
Abstract: This study investigated cross-sex best friendships in the experience and expression of jealousy within romantic relationships. Survey data (N = 346) revealed engaged-to-be-married individuals, compared to single, dating and married individuals, have the most negative attitudes regarding cross-sex best friendships. Results further indicated preventive jealousy experience is a predictor of rival-focused jealousy expression, and reactive jealousy experience is a predictor of both constructive and destructive jealousy expressions. Findings also suggest attitudes toward cross-sex best friendships can mediate the relationship between how jealousy is experienced and expressed in relation to reactive jealousy experience and destructive jealousy expression. Implications are discussed regarding how cross-sex best friendships can adversely affect romantic relationships.